2020
DOI: 10.3390/socsci9060097
|View full text |Cite
|
Sign up to set email alerts
|

Fostering the Social Development of Children with Special Educational Needs or Disabilities (SEND) through Dialogue and Interaction: A Literature Review

Abstract: The United Nations’ Sustainable Development Goal 4 stresses the importance of offering all students an inclusive, quality education, so that they can develop necessary life skills, including academic and social skills. Students with special educational needs and/or disabilities (SEND) not only have greater difficulties in their academic development, but they also have some social development limitations. It is therefore necessary to identify which strategies are effective in helping these students develop soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 70 publications
(125 reference statements)
1
9
0
Order By: Relevance
“…Additionally, it is worth highlighting that the benefits reported have been observed after only 6 months implementing DLGs (either face-to-face or online). Taking into account the benefits interactive learning has proven to have on students with special needs (Molina Roldán, 2015;García-Carrión et al, 2018;Fernandez-Villardon et al, 2020), having the possibility to transfer DLGs to the online modality as a way to maintain these interactions even in lockdown is important, on the one hand because school closure due to COVID-19 continues today in some contexts and, on the other hand, because new confinements could be applied in other contexts while the sanitary emergency continues. Our results open new opportunities for other schools teaching students with special needs to keep this environment of interaction, learning, and group cohesion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it is worth highlighting that the benefits reported have been observed after only 6 months implementing DLGs (either face-to-face or online). Taking into account the benefits interactive learning has proven to have on students with special needs (Molina Roldán, 2015;García-Carrión et al, 2018;Fernandez-Villardon et al, 2020), having the possibility to transfer DLGs to the online modality as a way to maintain these interactions even in lockdown is important, on the one hand because school closure due to COVID-19 continues today in some contexts and, on the other hand, because new confinements could be applied in other contexts while the sanitary emergency continues. Our results open new opportunities for other schools teaching students with special needs to keep this environment of interaction, learning, and group cohesion.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties to balance working from home while taking care of their children with disabilities have been pointed out (Hole and Stainton, 2020), as well as the loss of essential resources such as educators or structured learning environments (Masonbrink and Hurley, 2020). In addition, research done before the pandemic had shown the benefits interactive learning environments have on students with special needs, which improve the quality of the education these students are usually given (García-Carrión et al, 2018;Fernandez-Villardon et al, 2020). However, school closure and social distance may put in jeopardy these interactive environments that have been considered so important in special education.…”
Section: Impact Of School Closure On Students With Special Educationamentioning
confidence: 99%
See 1 more Smart Citation
“…According to Bruner (1996) , group work in schools in the form of communities of mutual learners allows for an equilibrium between individuality and group effectiveness, ensuring that everyone progresses according to their ability and giving all children the opportunity “to enter the culture with awareness of what it is about and what one does to cope with it as a participant” (p. 82). Interactive learning spaces, especially when they are mediated by dialogue, permit collective thinking and learning, enhance academic achievement, social skills, and social cohesion, and are especially beneficial for vulnerable groups of students ( Fernández-Villardón et al, 2020 ; García-Carrión et al, 2020 ). Hence, the objectives of inclusive education would be better attained when such interactive and dialogic learning environments are promoted.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, there has been a tendency to approach the coexistence in special education schools or classrooms in a more disciplinary way and from a more behavioral perspective, rather than from a social or dialogic one ( Beam and Mueller, 2016 ). However, there is increasing evidence of the relevance of interactions in the learning of children with disabilities ( García-Carrión et al, 2018 ; Fernández-Villardon et al, 2020 ), which play a key role in the development of both cognitive abilities and positive feelings, such as solidarity and friendship. But more research is needed to understand how this interaction-based learning can affect the prevention of violence with students with disabilities.…”
Section: Introductionmentioning
confidence: 99%